PENGARUH BLENDED LEARNING DALAM PEMBELAJARAN BERBASIS MASALAH (PBL) TERHADAP HASIL BELAJAR MAHASISWA IKIP MATARAM PADA MATERI PENCEMARAN LINGKUNGAN - Citra Ayu Dewi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
To teach environmental pollution subject material must be adjusted to real daylife problem because environmental pollution can’t last from human life. Associated with the characteristics of environmental contamination materials will be more appropriate if taught with problem-based learning strategies and to provide more learning opportunities, discussing the concept thoroughly, improve the transfer of learning and experience in leading the learning itself so that a blended learning is needed to be able to improve the process of critical thinking and lead to an optimal learning environment. This study has proved that the learning process that uses PBL and blended learning turned out to provide better student study result include cognitive, affective and psychomotor domains. In addition, the application of blended learning in PBL can also provide a positive perception.